The Wahls protocol [compact disc, unabridged] : how I beat progressive ms using Paleo principles and functional medicine - Wahls, Terry L. (Tantor Media, Inc., 2014)
An integrative approach to healing chronic autoimmune conditions by a doctor, researcher, and sufferer of progressive multiple sclerosis (MS) whose TEDx talk is already a web sensation.